East versus West: Energy intensity in coal-rich Europe, 1800–2000. (November 2018) - Nielsen, Hana; Warde, Paul; Kander, Astrid
Abstract: This paper presents a stylized graph of the energy intensities in two typical European sets of countries: the East and the West, in parallel to the existing research on the European North – South. The coal-rich West and East differ from the coal-poor South and North, in that their pattern is an inverted U-curve, while both North and South have consistently declining energy intensities. Energy intensity peaks about 50 years earlier in the West than in the East. For the first time we have been able to demonstrate that the gap between the West and East actually started in the 1950s, and to single out the main drivers behind the East European inefficiency. It was not general systematic wastefulness or lack of innovations, but surprisingly for a planned economy, it was the inefficiency in the expanding electricity system that accounted for most of the effect, together with the structural change towards heavy industrial production. As much of the industrial production became electrified and powered by less efficient electricity, this had a snowball effect through the whole value chain of the production. The negative impact of the planned economy on energy intensity was largest between 1948 and 1970. Highlights: Energy intensity in coal-rich West and East resembles an inverted U-curve. Energy intensity in the East diverges from the West after WII and peaks later. Planned economy had an impact on structural changes of the economy. No simple story of inefficient resource use and systematic waste. Inefficiencies were mainly concentrated in the electricity transformation sector.